COVID-19 waves: from face-to-face sessions and on-paper-based writing to online Open and Distance Learning sessions and on-screen-based jotting - Othman, Wan Norafikah (2024)
Coronavirus disease 2019 (COVID-19) is an infection caused by severe acute respiratory disease coronavirus 2 (SARS-CoV-2) (Rai et al., 2021). COVID-19 first emerged in Wuhan, China, in December 2019 before it was declared as a pandemic by the World Health Organization (WHO) on 11th March 2020 (Ochani et al., 2021). In Malaysia, the first confirmed case of COVID-19 was reported on 24th January 2020 (Aziz et al., 2020). Since then, Malaysia has experienced three waves of COVID-19 (Rampal & Seng, 2021). As a preventive measure against COVID-19, a series of Movement Control Order (MCO), Conditional Movement Control Order (CMCO), Recovery Movement Control Order (RMCO), Enhanced Movement Control Order (EMCO), Semi Enhanced Movement Control Order (SEMCO) and Full Movement Control Order (FMCO) has been enforced by the Malaysian government starting from 18th March 2020 until 14th June 2021 (Rama Naidu & Chelliapan, 2021) to limit the travel of people, thus minimizing the spread of COVID-19. The National Recovery Plan (NRP) has then taken place starting from 15th June 2021 until 31st December 2021 (Tang, 2021) to allow the country to revive from the COVID-19 pandemic and the people to adapt to the new life and economic status.